Potabilidade da água após reservação domiciliar : a percepção do morador - Ferreira, Cibele Esmeralda Biondi (2017)
Water is a fundamental asset to life and its direct relationship with the promotion of human health is undeniable. In addition to prevention and care actions, it is considered increasingly important to act on the determinants of health. The literature records studies showing the risk that the population is exposed due to the presence of the domestic water reservoir and the lack of necessary care, and that the problem is found inside the residences, because the water collected inside the domestic reservoirs often does not conform to the standards of potability. This study intends to investigate the residents' perceptions regarding the responsibility for water use and the maintenance of the reservoirs in order to guarantee the potability of the water after domestic reservation inside the residences supplied by the concessionaire in two districts in the city of Vitória, Espírito Santo. The research universe consisted of single family dwellings presented according to the standard typologies for urban buildings defined by Brazilian norm. The analysis of the data was performed following the steps of the content analysis proposed by Bardin and through analysis with the help of the Microsoft Office Excel program. This study allowed the proposal of an information technology aimed at guiding the correct actions directed to the good practices regarding the periodic cleaning in the reservoirs of potable water inside the residences, in order to guarantee the potability of the water after the home reservation and emphasizes the importance of the review of how the information is being conveyed in such a way that the resident knows the operation of the reservoir, feels responsible for guaranteeing the potability of the water inside your residence, and broadens the exercise of your citizenship, being a protagonist and contributing to the protection of public health and urban health.